Programmed cell death of larval tissues induced by juvenile hormone in the bamboo borer, Omphisa fuscidentalis - Manaporn Manaboon (2018)
Programmed cell death (PCD) plays a critical role during animal development through the destruction of unneeded cells and tissues. In some insects, the prothoracic glands (PGs) and anterior silk glands (ASGs) are larval-specific tissues that are normally eliminated by PCD after pupation. Previous studies report that juvenile hormone analog (JHA) terminates the larval diapause of Omphisa fuscidentalis by increasing the hemolymph ecdysteroids that trigger PCD. Because JHA may indirectly induce the PCD of the PGs and ASGs of Omphisa diapausing larvae, the effects of JHA on the induction of PCD were determined. The application of 1. μg JHA induced PCD in the PGs and ASGs of larvae identified as stage G0 (prior to pupation). The injection of 1. μg 20E triggered the PCD of the ASGs when the larvae expressed a G0-G1 morphology, whereas PCD occurred in the PGs on day 1 post-injection. Histological studies revealed similar patterns of morphological changes during the PG and ASG PCD in the JHA- and 20E-treated larvae. Furthermore, to confirm that PCD was induced by a high ecdysteroid level that increases after JHA application, the expression profiles of EcR-A and EcR-B1 in the PGs and ASGs from the JHA-treated larvae were examined, and the results showed that the expression levels of EcR-A and EcR-B1 mRNA increased during the G0 stage. These results suggest that JHA may be involved in PCD by increasing the ecdysteroid titer, leading to termination of the larval diapause period in Omphisa fuscidentalis. © 2012 Elsevier Ltd.